Wooing the witch queen - Burgis, Stephanie (Burgis, Stephanie. Queens of Villainy, 2025)
"Queen Saskia is the wicked sorceress everyone fears. After successfully wrestling the throne from her evil uncle, she only wants onething: to keep her people safe from the empire next door. For that,she needs to spend more time in her laboratory experimenting with her spells. She definitely doesn't have time to bring order to her chaotic library of magic. When a mysterious dark wizard arrives at hercastle, Saskia hires him as her new librarian on the spot. "Fabian"is sweet and a little nerdy, and his requests seem a little strange- what in the name of Divine Elva is a fountain pen? - but he's getting the job done. And if he writes her flirtatious poetry and his innocent touch makes her skin singe, well... Little does Saskia knowthat the "wizard" she's falling for is actually an Imperial archduke in disguise, with no magical training whatsoever. On the run, withperilous secrets on his trail and a fast growing yearning for the wicked sorceress, he's in danger from her enemies and her newfound allies, too. When his identity is finally revealed, will their love save or doom each other?"--